Experimental Realization of Finger Gesture Recognizing Glove Sensor for Deaf and Dumb Person - Kumar, Vikash (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
A majority of the human beings on this planet are deaf and dumb. The exchange of information between a deaf persons who knows sign language and the person doesn't poses a serious problem for them as compared to between who doesn't know the sign language. Since communication is the fundamental and one of the very important things to have in life therefore the person who doesn't know sign language feels alien in the atmosphere he lives in. Sign language is the non-verbal form of language which uses hand gestures to express feelings and to convey information and sign language is very popular among deaf community. This paper aim is to create a helping hand glove sensor for deaf people to communicate easily with other people. The glove has five flex sensors which are glued along lengths of five fingers on the glove. The glove produces a proportional change in resistance for every particular gesture. The analogue values which are the output of the sensors are converted into digital format. These gestures are analyzed using Arduino controller. This board compares the predefined voltage levels stored in the memory with the output of the flex sensor. And thus according to that a suitable match is found and a particular sentence is displayed on the LCD and also can be heard on the speaker. This is how the proposed sensor helps the deaf people to make their life easier than before and brings new colors to their life.